Comparison of oral feeding of peptide and amino acid meals to normal human subjects. Issue 4 (April 1979) - Silk, D. B. A.; Chung, Y. C.; Berger, K. L.; Conley, K.; Beigler, M.; Sleisenger, M. H.; Spiller, G. A.; Kim, Y. S.
Abstract : Intestinal perfusion studies performed in man have suggested that amino acid nitrogen may be absorbed more rapidly from peptides than free amino acids. The aim of the present study was to compare the effects of the oral administration of peptides and free amino acids. Two isonitrogenous liquid test meals, one containing 50 g of a partial enzymic hydrolysate of fish protein in which approximately 80% of the nitrogen content was present as small peptides (peptide meal), and the other a mixture of free amino acids (amino acid meal) the composition and molar pattern of which simulated that of the peptide meal, were administered on separate occasions to six normal subjects intubated with a triple lumen tube. Both meals contained the reference marker polyethylene glycol. Fractional absorption of amino acid residues one and two hours after ingestion of the two meals was similar at three intestinal locations situated 120, 160, and 200 cm from the mouth of each subject, and at two hours 73·8% and 72·0% of the amino acid residues had been absorbed respectively by the time the contents of the peptide and amino acid meals reached the middle sampling port of the tube. The total sum of individual amino acid increments in plasma was significantly greater 30 minutes (p < 0·025) and one hour (p < 0·05) after ingestion of the peptide than amino acid meals. By three hours the total area under the two plasma curves was similar. Normal human subjects thus appeared to be capable of assimilating orally administered mixtures of peptides and free amino acids with equal efficiency. Secretion of fluid into the lumen of the upper small intestine, assessed by reference to dilution of the polyethylene glycol, was less after ingestion of the peptide meal. In clinical situations characterised by fluid and electrolyte malabsorption consideration might be given to using small peptides rather than free amino acids as the nitrogen source in nutritional diets.